Root cause failure analysis : a guide to improve plant reliability - Sahoo, Trinath (Wiley, 2021)
"Process equipment and piping systems constitute the major portion of plant assets and their integrity and reliability are essential for plant availability and performance. Many of these systems are subjected to hazardous service conditions and damage mechanisms which if not adequately monitored and assessed could result in major failures with consequential significant injuries and business losses. Root cause analysis helps in taking proactive steps to inspect the process equipment and piping system before any abnormal conditions happen which may lead to equipment damage."-- Provided by publisher
Keywords: Root cause analysis.; Piping.; Industrial equipment.; elektronické knihy; electronic books